Use of 3-Hydroxy-3-Phenyl-1-m-Hydroxyphenyltriazene in the Spectrophotometric Determination of Cobalt(II) - Sharma, Kavita; Maroo, Usha; Chauhan, R.S.; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
The tile reagent has been used for spectrophotometric determination of Co(II). The composition of yellow coloured complex has been found to be 1 : 2 (Co : R) with absorption maximum at 404 nm in the pH range 6.80-7.45. Absorbance measurements were made at 412 nm. Beer's law was followed in the studied concentration range 5.0 x 10–6 M to 3.0 x 10–5 M. The value of molar absorptivity, Sandell's sensitivity, stability constant (log β) and free energy of formation were found to be 20,000 L/mole cm, 2.94 ng/cm2, 10.18 and -13.88 kcal/mole respectively. Interference of twentyfive diverse ions has been examined.